Preferences of Transcultural Diversity: The Idea of City Diplomacy - Ryniejska-Kiełdanowicz, Marta; Ratajczak, Magdalena (Political Preferences, 2019)
Cities create a transcultural sphere and a platform for transcultural dialogue.Cities play an important cultural-creative role and they try to become policy player onat the international level. The aim of this study is to evaluate the actions taken in cities from two perspectives. On the one hand how the multicultural (multi-lingual and multi-religious) cityscape is shaped, how the city is governed in order to create a space termed as a ‘meeting place’. On the other hand how these undertakings affect the image of the city on the international stage and how they contribute to the city diplomacy strategy.